HEALTH-PRENEURSHIP: MENGAPA ILMU KESEHATAN MASYARAKAT MEMBUTUHKAN SEORANG ENTREPRENEUR? - Jodi Visnu (Bahasa Indonesia, 2020)
Introduction: In recent years, the business world has been increasingly sought after by young people from various educational backgrounds. The world of medicine also has to deal with business competition, especially in the provision of health services. In essence, medical students learn about business in the Public Health Science curriculum through the theory of management. However, this cannot be fully realized due to the limitations of the learning curriculum. The health business should go alongside not only holistic and high-quality health services, but also good doctor-patient communication, so that the therapeutic process may be more effective and adverse outcomes such as client dissatisfaction leading to a medical malpractice claim are prevented. Objectives: This article is used as a teaching material for health-entrepreneurship lectures that aim to explore entrepreneurship in the health sector, to identify the potential role of public health in the business world for the learning of medical students, and to stimulate students to come up with new innovative ideas and spark creativity to produce a high-quality invention. Method: The writing of this article used the narrative review method as part of the literature study. Discussion: Health-entrepreneurship is closely related to public health science. In this curriculum, students can learn about marketing, especially communication within the context of health promotion that focuses on market demand. A health-entrepreneur is expected to maintain the marketing principles within the boundaries of medical ethics and trained to be a practitioner as well as a problem solver. Potentially he is also expected to become a public health entrepreneur who can develop knowledge in the field of epidemiology, environmental health, biostatistics, health policy, health-care management, and social and behavioral sciences.